The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c6ra27730f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selenium and polysaccharide of Atractylodes macrocephala Koidz. (PAMK) on endoplasmic reticulum stress and apoptosis in chicken spleen induced by heat stress

Abstract: Endoplasmic reticulum (ER) stress and oxidative stress are involved in different types of stress induced injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…For example, many studies in broilers showed that the dosage of Se, added at a range of 0.3-1.0 mg/kg to the diet, improved the growth performance of chicken and quails when exposed to heat stress, contributing to the improvement of immune function and the increased activities of glutathione, GSH-Px, and SOD (47)(48)(49)(50)(51)(52)(53). It is also implied that a greater amount of Se is required for enhancing selenium-dependent antioxidant enzyme activities and gene expression relative to the glutathione system to alleviate oxidative damage induced by heat stress in poultry (54)(55)(56)(57)(58)(59). According to the positive result of antioxidant ability, we will further investigate the Se requirement as well as the effect of Se yeast supplementation in diets in duck layers under heat-stressed condition in our next study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies in broilers showed that the dosage of Se, added at a range of 0.3-1.0 mg/kg to the diet, improved the growth performance of chicken and quails when exposed to heat stress, contributing to the improvement of immune function and the increased activities of glutathione, GSH-Px, and SOD (47)(48)(49)(50)(51)(52)(53). It is also implied that a greater amount of Se is required for enhancing selenium-dependent antioxidant enzyme activities and gene expression relative to the glutathione system to alleviate oxidative damage induced by heat stress in poultry (54)(55)(56)(57)(58)(59). According to the positive result of antioxidant ability, we will further investigate the Se requirement as well as the effect of Se yeast supplementation in diets in duck layers under heat-stressed condition in our next study.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that PAMK can relieve the HS-induced oxidative stress in the chicken spleen. Furthermore, previous studies also stated that PAMK may antagonize apoptosis in the chicken [ 36 , 40 ]. In the present study, PAMK decreased the expressions of pro-apoptotic genes, and increased the expression of anti-apoptotic gene.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that GRP78 expression was increased by the pyrrolidine dithiocarbamate/Cu complex [21]. The expression GRP78 was significantly elevated in the spleen of chicken induced by heat stress [22]. In pig, the CHOP protein content was increased following exposure to the high temperature [7].…”
Section: Discussionmentioning
confidence: 99%